2016
DOI: 10.13064/ksss.2016.8.1.045
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of consonant deletion in the word-internal onset position: Evidence from spontaneous Seoul Korean speech

Abstract: This study examined the deletion of onset consonant in the word-internal structure in spontaneous Seoul Korean speech. It used the dataset of speakers in their 20s extracted from the Korean Corpus of Spontaneous Speech (Yun et al., 2015). The proportion of deletion of word-internal onset consonants was analyzed using the linear mixed-effects regression model. The factors that promoted the deletion of onsets were primarily the types of consonants and their phonetic contexts. The results showed that onset deleti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The Korean Corpus of Spontaneous Speech (Yun et al, 2016) showed high percentages of labeling consistency for the analysis of the present study. There were nine labelers for the corpus, and the percentage agreement of transcription was 98.1% for all segments (i.e., the detailed segments: stops, 99.1%; fricatives, 98.6%; affricates, 98.3%; nasals, 96.6%; liquids, 99.5%; and vowels, 97.7%) …”
Section: Speech Materialsmentioning
confidence: 83%
See 1 more Smart Citation
“…The Korean Corpus of Spontaneous Speech (Yun et al, 2016) showed high percentages of labeling consistency for the analysis of the present study. There were nine labelers for the corpus, and the percentage agreement of transcription was 98.1% for all segments (i.e., the detailed segments: stops, 99.1%; fricatives, 98.6%; affricates, 98.3%; nasals, 96.6%; liquids, 99.5%; and vowels, 97.7%) …”
Section: Speech Materialsmentioning
confidence: 83%
“…The reduction processes of segments frequently occur in spontaneous or conversational speech (Bell et al, 2009;Dilts, 2013;Johnson, 2003;Keating, 1998;Kim et al, 2016;Raymon et al, 2006;Yao, 2001). Johnson (2003) showed the extreme version (i.e., deletion) of consonants and vowels in conversational American English; for example, the word "probably" underwent a series of reductions such as [prɑbəbli] -[prɑbli] -[prɑli] - [prɑ].…”
Section: Introductionmentioning
confidence: 99%